Forensic Genetics and Genomics in Peru: Current situation and future challenges: La Genética y Genómica Forense en el Perú: Situación actual y desafíos futuros - Neyra Rivera, Carlos David (2024)
Forensic Genetics is defined as a field of knowledge that uses both genetic concepts and molecular tools. This is used to resolve cases in which it is desired to identify the identity of people allegedly involved in a criminal act, kinship ties, identification of missing persons, etc. Currently, Forensic Genetics mainly uses molecular markers of the type STRs (short tandem repeats), SNPs (single nucleotide polymorphisms) and insertion/deletion INDELs)(1). In order to use these markers, it generally begins with DNA extraction, a multiplex polymerase chain reaction, capillary electrophoresis and analysis with specialized software to obtain a genetic profile that is unique for each individual.